Pelaksanaan Metode Wahdah Pada Tahfidz Qur’an Dalam Program Madrasah Diniyah Takmiliyah Wustha Di SMP Negeri 4 Tualang Kab. Siak Provinsi Riau - Nur Faridah; Muhiddinur Kamal; Salmi Wati; Deswalantri Deswalantri (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
The background for writing this thesis is that the implementation of the Tahfidz Qur'an in the Madrasah Diniyah Takmiliyah Wustha Program at SMP Negeri 4 Tualang is held on Monday-Thursday, the implementation time is 15.00-16.30. In this Tahfidz Qur'an activity, the Wahdah method is used. The Wahdah method is a way to memorize the Al-Qur'an one by one for the verses you want to memorize by reading them 10 to 20 times to form a pattern in the image. This research aims to see how the wahdah method is implemented in tahfidz Qur'an in the Madrasah Diniyah Takmiliyah Wustha Program. The approach used in this research is a qualitative approach, meaning that the researcher looks at the implementation of the wahdah method used by Tahfidz teachers. This research uses qualitative descriptive research. The key informant in this research was the Tahfidz teacher at SMP Negeri 4 Tualang, while the supporting informants were class VIII students at SMP Negeri 4 Tualang. Observation, Interview and Documentation data collection techniques. Data validation technique: triangulation technique. data analysis techniques: data presentation, data selection, and conclusion drawing. Based on the findings of research conducted by the author, the results show that: in the 2023/2024 academic year, teachers changed the system with the first 3 months focusing on Tahfidz Qur'an only to achieve the target of Siak, namely a minimum of students memorizing 1 juz. After the initial 3 months ended, students returned to studying as before, namely studying the subjects of Fiqh, Aqidah Akhlak, Al-Qur'an Hadith, Tarekh and Arabic. The steps for implementing the Wahdah Method at SMP Negeri 4 Tualang are, memorizing verse by verse and confirming the reading. In carrying out tahfidz Qur'an activities using the wahdah method, it has several benefits, namely making it easier for students to memorize, their memorization memory is stronger, some students get the letters correct. At the beginning of the first month it went well using this method. Then students feel bored in using this method. Because there are some students whose memorization is quite far, because using this method students feel they cannot increase their memorization deposit, because this method memorizes surahs together. The solution is to exchange or combine the wahdah method with another method. Or change the method in tahfidz Qur'an.